Circostanze del reato: trasformazioni in atto e prospettive di riforma - Pellegrini, Lorenzo (Premio Tesi di Dottorato, 2014)
The circumstances of the crime contribute both to a best individualisation and definition of the case, and to the judicial assessment of the fine. This double "soul" makes the circumstances of the crime an elected ground for policies that are either legalitarian (policies of legal determination of the particular case and legal quantification of the fine), or of judicial discretion (judicial determination of the particular case and judicial assessment of the fine). The uncertain amendment has, however, delivered a magmatic and unbalanced system. The work tries to give rationality to the matter by affirming that a reform of the institute (no longer postponable) must first pass by the special part of the code, through a redefinition of the legal notes and then by the assessment system as a whole. However, such an intervention would make the institution of circumstances seem irrational, leading it to radical suppression.